Codevelopment action learning for business co-create, accelerate, grow - Paquet, Maxime; Sabourin, Nathalie; Lafranchise, Nathalie, 1968-; Cheshire, Ron (New York, NY : Routledge, 2024)
"Workplaces where the focus is on innovation, teamwork and learning have become a reality, thanks to a simple, practical, and effective approach. This book will help you to create a collaborative and empowering culture in your organization. The CAL method, tools, and theoretical foundations for each component are presented in detail here. Real case studies and research findings on the tangible benefits and impacts of the approach enrich its content. Authored by a dynamic team of CAL business coaches and academics, the knowledge is shared in a straightforward and accessible manner. Business leaders, entrepreneurs, human resources and learning professionals, coaches, facilitators, scholar practitioners, and more will welcome this book's thought-provoking guidance to co-create solutions, accelerate goals, and grow capabilities for the 21st century"--
Keywords: Teams in the workplace; Technological innovations -- Management; Corporate culture; Active learning; BUSINESS & ECONOMICS / Decision-Making & Problem Solving